(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2022)
I am delighted to learn that Trinity Institute of Profcssional Studies is organizing its 11th national conference TIPSCON in online mode , on the theme of ’’ Resilience & Reinvention : A Path For Change in Management , IT,Media and Low’’As the working dynamics are quickly evolving ,with many organisations trying to navigate through unfolding business complexities, focus has been shifted to how will we bounce back from how will this affect us.Digital transformation has occurred almost on the fly in recent times.To be resilient and prepare for a new way of opreating,change has had to come quickly and effectively in almost all the fields of the industry .